1990
DOI: 10.1159/000235141
|View full text |Cite
|
Sign up to set email alerts
|

Human Recombinant Lymphokines and Cytokines Induce Pulmonary Eosinophilia in the Guinea Pig which Is Inhibited by Ketotifen and AH 21–132

Abstract: Subcutaneous or intraperitoneal injection of recombinant human granulocyte-macrophage colony-stimulating factor, interleukin 3, or mouse tumour necrosis factor alpha, but not recombinant human interferon gamma, platelet-derived growth factor, or transforming growth factor beta caused selective eosinophilia of the pulmonary airways in the guinea pig. Unlike responses to latelet-activating factor, there was no attendant detectable airway hyperreactivity, but in common with responses to platelet-activating factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 41 publications
3
11
0
Order By: Relevance
“…While in the present study both heparin and Org 10172 inhibited the infiltration of inflammatory cells into the airways following PAF challenge, it appears that the inhibitory effect of heparin on PAF-induced airway hyperresponsiveness is not dependent on this anti-inflammatory effect as polyglutamic acid substantially inhibited cell infiltration without inhibiting the associated airway hyperresponsiveness. These results, separating the induction of bronchial hyperresponsiveness from inflammatory cell infiltration, support previous work in this model with other drug classes (Spina et al, 1991;Herd et al, 1992) and in other experimental (Ladenius & Biggs, 1989;Kings et al, 1990;Sanjar et al, 1990;Matsuse et al, 1991) and clinical (Lundgren et al, 1988;Gibson et al, 1989) situations, showing that eosinophils may not be a prerequisite for the induction of airway hyperresponsiveness.…”
Section: Bronchoalveolar Lavagesupporting
confidence: 90%
“…While in the present study both heparin and Org 10172 inhibited the infiltration of inflammatory cells into the airways following PAF challenge, it appears that the inhibitory effect of heparin on PAF-induced airway hyperresponsiveness is not dependent on this anti-inflammatory effect as polyglutamic acid substantially inhibited cell infiltration without inhibiting the associated airway hyperresponsiveness. These results, separating the induction of bronchial hyperresponsiveness from inflammatory cell infiltration, support previous work in this model with other drug classes (Spina et al, 1991;Herd et al, 1992) and in other experimental (Ladenius & Biggs, 1989;Kings et al, 1990;Sanjar et al, 1990;Matsuse et al, 1991) and clinical (Lundgren et al, 1988;Gibson et al, 1989) situations, showing that eosinophils may not be a prerequisite for the induction of airway hyperresponsiveness.…”
Section: Bronchoalveolar Lavagesupporting
confidence: 90%
“…T-cell derived cytokines such as GM-CSF, IL-3 and IL-5 have pronounced effects on neutrophils and eosinophils, including chemotaxis, prolongation of survival and activation (Corrigan & Kay, 1992). Human recombinant GM-CSF and IL-3 have been shown to induce eosinophilia in the guineapig (Kings et al, 1990) and intra-tracheal injection of murine recombinant (mr) IL-5 induced a significant cellular infiltration into guinea-pig lungs (Iwama et al, 1992). It is interesting to note that there was a significant increase in lymphocytes counts in BAL fluid from Sephadex-injected guinea-pigs although the role of these cells in the model is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Pretreat ment with aminophylline, ketotifen or dexamethasone prevented eosinophilia but not hyperreactivity. Following subcutaneous or intraperitoneal administration of recom binant human granulocyte-macrophage colony-stimulat ing factor or interleukin-3 in guinea pigs, Kings et al [24] reported eosinophilia in the BALF but found no signs of increased bronchial reactivity to i.v. histamine.…”
Section: Discussionmentioning
confidence: 99%